Crystallization of para -aminobenzoic acid forms from specific solvents - Hussain, Mohammed Noorul; Van Meervelt, Luc; Van Gerven, Tom (CrystEngComm, 2024)
para -Aminobenzoic acid ( p -ABA) is a pharmaceutical compound with a challenging polymorph nucleation behavior. It has 4 polymorphs and multiple solvates. Among these forms, the α and the β form are subjects of interest for research in many studies. The α form nucleates predominantly in many solvents. The β form is known to nucleate in only 2 solvents. The reasoning for this was that the solvents, having a strong interaction with the COOH group, inhibit the dimerization of the COOH group leading to the nucleation of the β form. Following this reasoning, in this work, DMSO and DMF, which have strong interaction with the COOH group, were tested as solvents for anti-solvent crystallization experiments. Water was used as anti-solvent. The goal was to investigate the resultant polymorph nucleation under such specific solvent–solute interaction. Results showed that with DMSO as solvent at higher anti-solvent volume fraction the α form nucleated predominantly. At lower volume fractions there was no nucleation normally but addition of some seeds quickly led to β form nucleation. With DMF, a special result was seen where a new solvate between p -ABA and DMF was discovered. Single crystal XRD results confirmed that the formation of the solvate was a result of hydrogen bonding between the solute and the solvent. Overall, the results do confirm that solvents having strong interaction with the COOH group can lead to nucleation of forms other than the persistent form.